Determinants of Health and Physical Activity Levels Among Breast Cancer Survivors During the COVID-19 Pandemic: A Cross-Sectional Study - Gurgel, Aline Rachel Bezerra; Mingroni-Netto, Pedro; Farah, Jose Carlos; de Brito, Christina May Moran; Levin, Anna S.; Brum, Patricia Chakur (Frontiers in Physiology, 2021)
Background: Increased exercise and physical activity levels are recommended throughout cancer therapy and survivorship. Nonetheless, COVID-19 pandemic and consequent social distancing are likely to cause a decline in physical activity. Objective: to evaluate the level of unsupervised physical activity of breast cancer survivors during the COVID-19 pandemic, and the factors associated with difficulties in engaging and maintaining recommended physical activity levels. Methods: This is a cross-sectional epidemiological study with a sample of 37 breast cancer survivors. They participated in a canoeing training program (Remama group) at the University of Sao Paulo before the COVID-19 pandemic. Socioeconomic aspects, engagement in physical activity, motivation, and potential exposure to COVID-19 were investigated through an online survey, administered in September of 2020. Results: During the pandemic, participants increased their body weight (5±3.4 kg); 90% reported decreasing physical activity levels associated with increased sedentary time. Twenty-one (58%) participants exhibited some COVID-19-related symptom, most used public transportation (59%) or returned to work during the period of high incidence of COVID-19. The only factor associated with perceived difficulty in engaging in physical activities was having had more than 3 cancer treatments (RR: 2.14; 95%CI: 1.07-4.27). Conclusion: The COVID-19 pandemic led to a group of previously active breast cancer survivors to decrease their physical activity, gain weight, and have sedentary behaviour. Specific tailored-care interventions are needed to prevent these occurrences, as overweight and physical inactivity may impose additional risk for a severe course of COVID-19 in cancer patients.